Carbono Azul no Semiárido Nordestino: estoque de carbono do solo de um manguezal em recuperação no estuário do Rio Pacoti, CE - Rodrigues, José Vítor Machado (2022)
Mangroves occupy a global area of approximately 137,000 km2, covering at least 124 countries located in tropical and subtropical regions. In addition to being important habitats for several species and providing important ecosystem services for humans, mangrove forests, as well as salt marshes and seagrasses, have been the focus of much attention for accumulating large amounts of carbon for centuries (and even millennia) in its biomass and soils. As they are efficient sinks, they are, consequently, important mitigators of global climate change when conserved. In this study, the soil carbon stock was estimated in a mangrove area impacted by old salt ponds, in the semi-arid northeast of Brazil. The mangrove area of the Pacoti River (CE), which is currently undergoing an ecosystem recovery process, shows significant variations (p < 0.05) in soil density, concentration and stock of organic carbon (Corg) among the sampled areas. Stocks in the top meter layer of soil ranged from 14 to 290 MgC/ha. These values correspond to the degraded hypersaline tidal flat and the preserved fringe mangrove area (Rhizophora mangle), respectively. For the preserved mangrove, the stocks were higher than that of the Amazonian mangroves and close to the global average (283 ± 193 Mg C/ha). On the other hand, the average stock of Corg in the area impacted by salt farming is 17.55 ± 4.52 Mg C/ha. This stock, similar to that of degraded areas of estuaries in Ceará and semi-arid regions of West Africa, Australia and the Red Sea coast, is considerably lower than the global average and highlights the impact caused by land use change and extreme climatic conditions in the region. For the Pacoti River mangrove, it is estimated that about 836.76 Mg CO2 e/ha were lost to the atmosphere as a result of human activities. This research brings discussions based on a review of blue carbon stocks in mangroves of Brazil, which is based on 17 articles containing information on 8 states. Finally, this study reinforces the importance of semi-arid mangroves as efficient sinks, even under environmental conditions that limit plant development, and points out the urgency of integral protection of these ecosystems, in order to preserve the capacity of carbon sequestration and storage, mitigate the effects of climate change and improve mangrove management and recovery projects.